Working procedures for cocoa germplasm evaluation and selection - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Proceedings of a workshop, held 1 6 February 1998 in Montpellier, France and organised by the Common Fund for Commodities (CFC), International Cocoa Organisation (ICCO) and the International Plant Genetic Resources Institute (IPGRI).Edited by A...